The Influence of Education, Age, Extension Services, and Experince on the Management of Small Holder Palm Oil Farms in Gunung Meriah Sub-district, Deli Serdang Regency - Sihombing, Yessyca Agustine; Manurung, Hamzah (Lembaga Teewan Journal Solutions, 2026)
In many plantation sectors, Indonesia plays a vital role in creating employment opportunities, generating foreign exchange, and supplying raw materials to industry. One factor contributing to low productivity is the level of education among farmers. Another constraint is age; extension services and experience in farming act as barriers, as age is closely linked to productivity performance, whilst extension services are a key element in determining productivity and serve as a medium for the transfer of knowledge and technology; experience significantly influences farmers’ ability to manage palm oil plantations and address challenges. In this study, the researcher aims to conduct empirical research by directly examining how palm oil plantation productivity relates to the key factors under investigation, such as age, education, extension services, and experience. The study is titled “The Influence of Education, Age, Extension Services, and Experience on the Management of Small Holder Palm Oil Farms in Gunung Meriah Sub-district, Deli Serdang Regency”.